The Effectiveness of Online Problem-Based Learning in Improving Critical Thinking Skills and Digital Literacy of Elementary School Students - Herwinta Inggil Rejeki; Joko Sutarto; Budi Naini Mindyarto (Journal of Primary Education, 2022)
Online learning is a learning process that is far from the center of education and is independent. Critical thinking skills and digital literacy are considered as 21st century skills. This study aims to test and analyze the effectiveness of online problem-based learning in improving students' critical thinking skills and digital literacy skills. The design of this study was a quasi-experimental design in the form of a nonequivalent control group design. The subjects in this study were fifth grade students of Gugus Muhammad Syafei. The data from the expert validation were analyzed using a quantitative descriptive method. The thinking ability of the experimental class students at the pretest was 59.83 and increased at the posttest by obtaining an average score of 75.67. While the critical thinking skills of the control class on the pretest obtained an average of 52.96 and increased at the posttest of 64.07. The result of the value of Sig.(2-tailed) is 0.000. The digital literacy skills of experimental class students at the pretest of 40.53 got an increase in the posttest by reach an average score of 50.77. While the digital literacy skills of the control class in the pretest reached an average of 33.33 and increased at the posttest by 40.00. The result of the Sig. (2-tailed) is 0.001. Based on these results, it can be concluded that there is a significant effect in the application of the online problem-based learning model on improving students' digital literacy skills.